Pemberdayaan Guru Dalam Pengelolaan Pengembangan Sekolah: Studi Kualitatif Tentang Profesionalisme Guru di SMAN 1 Panyipatan (Equilibrium: Jurnal Pendidikan, 2025)
Teachers have a strategic role in improving the quality of education, not only as implementers of learning, but also as drivers in the management and development of educational institutions. This study aims to explore the form of teacher empowerment in managing school development at SMAN 1 Panyipatan. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The results showed that teachers were empowered through active involvement in the School Development Team, internal training, and the implementation of strategic school programs. This empowerment contributed to increased motivation, sense of ownership, and overall school performance. These findings emphasize the importance of the participatory empowerment model as a strategy to strengthen teacher professionalism and encourage the achievement of educational institution performance.Pemberdayaan Guru Dalam Pengelolaan Pengembangan Sekolah: Studi Kualitatif Tentang Profesionalisme Guru di SMAN 1 Panyipatan